BENTUK DAN FUNGSI TARI MAESWARA SWATANTRA NJUK LADANG DI KABUPATEN NGANJUK - Delima Indra Prasta; F. Hari Mulyatno (Greget, 2019)
AbstractMaeswara Swatantra Anjuk Ladang Dance is a new creation dance created by Didik Purwanto in Nganjuk regency. The dance was rushed by 7 female dancers using the Bokor property. This research will essentially reveal about the form and function of the Maeswara Swatantra Anjuk Ladang dance in Nganjuk district. The research uses foundations of theory to dissect Problem forms used Sri Rochana Widyastutieningrum concept about the physical form and the form of the reveal. To dissect function problems, this study uses function theory Soedarsono on the function of the show is divided into two namely function Primary and secondary functions. The primary function is divided into 3 namely (1) As a ritual means, (2) as a means of personal entertainment and (as Aesthetic presentation facilities. Secondary functions are such as education, propaganda, Legation, and Identity of an area. The methods used in this study Qualitative method with an ethnokoreological approach through various stages of observation, data collection and data writing. The results of this study showed that the Maeswara Swatantra Anjuk Ladang Dance is a themed group dance that serves as a welcome guest as well as the regional imaging of Nganjuk regency.Keywords: forms, functions, dance Maeswara Swatantra Anjuk Ladang.